2007
DOI: 10.1002/pros.20641
|View full text |Cite
|
Sign up to set email alerts
|

HIF‐1α promotes survival of prostate cells at a high zinc environment

Abstract: These results suggest that HIF-1alpha functions as an intrinsic defense molecule that enables prostate cells to survive in a zinc-rich environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…The sections were deparaffinized, rehydrated through a graded alcohol series and heated in 10 mM sodium citrate (pH 6.0) for 5 min in a microwave to retrieve the antigens. Nonspecific sites were blocked with a solution containing 2.5% bovine serum albumin (SigmaAldrich) and 2% normal rabbit serum in PBS (pH 7.4) for 1 h, and the sections were then incubated overnight at 4°C with anti-HIF-1α (Santa Cruz) or anti-PCNA (Santa Cruz) antibody diluted 1:100 in blocking solution [17]. As negative controls, sections were incubated in blocking solution without primary antibody.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The sections were deparaffinized, rehydrated through a graded alcohol series and heated in 10 mM sodium citrate (pH 6.0) for 5 min in a microwave to retrieve the antigens. Nonspecific sites were blocked with a solution containing 2.5% bovine serum albumin (SigmaAldrich) and 2% normal rabbit serum in PBS (pH 7.4) for 1 h, and the sections were then incubated overnight at 4°C with anti-HIF-1α (Santa Cruz) or anti-PCNA (Santa Cruz) antibody diluted 1:100 in blocking solution [17]. As negative controls, sections were incubated in blocking solution without primary antibody.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…This leads to the possibility that in the natural environment of the prostate gland, the normal glandular epithelial cells may incorporate increased Bcl-2 production and/or antiapoptotic responses, which could prevent the potential apoptotic cytotoxic effect of zinc. The report of Park et al provided evidence for a protective effect of increased HIF1α against cytotoxicity resulting from high zinc levels in prostate cells [32]. Pursuant studies identified the anti-apoptogenic agent, survivin, as a mediator of HIF1α protection of prostate cells from zinc cytotoxicity [33].…”
Section: Factors and Conditions That Protect Cells From The Cytotoxic Ementioning
confidence: 99%
“…In fact, we previously reported the HIF-1α-inducing activity of Py-Zn in various cell lines, such as PC3, DU145, MKN28, and HEK293 cells [15]. In that study, we used Py-Zn as a zinc ionophore to transport Zn 2+ into cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given the previous reports, we tested four compounds as HIF-1α inducer candidates, namely, bafilomycin A1 [12], baicalein [13], EGCG [14], and Py-Zn [15]. The molecular structures of the test compounds are illustrated in Fig.…”
Section: Test Compoundsmentioning
confidence: 99%